Mendelian randomization study showed no causality between metformin treatment and polycystic ovary syndrome. - Liting Lin; Huan Shen; Yanbin Wang (PLoS ONE)
Background Despite previous clinical studies providing some evidence of an association between metformin treatment and polycystic ovary syndrome(PCOS), these findings remain controversial. To investigate whether the association reflect causality, a two-sample Mendelian randomization (MR) method was conducted. Methods Data from genome-wide association studies were analyzed, with the exposure factor being metformin and the outcome variable being PCOS. The inverse variance weighted(IVW) was used as the primary method for MR analysis. In addition, MR-Egger, weighted median, heterogeneity tests, and sensitivity analyses were performed. Results The initial and validation MR analyses indicated that genetically predicted metformin treatment had no effects on PCOS. Sensitivity analyses provided additional confirmation of the reliability of the MR results. Conclusions Our two-sample MR analysis did not find genetic evidence supporting a significant association between metformin treatment and PCOS.